Reliability of prestressed concrete girders design: Comparison between NBR and Eurocode codes - Avila, Vinicius Heidtmann; Real, Mauro de Vasconcellos (International Journal of Advanced Engineering Research and Science, 2022)
This work evaluates the reliability index of prestressed girders beams of highway bridges designed according to Brazilian and European codes concerning the bending ultimate limit state. A model was used to verify the resistant capacity of the beams in the bending ultimate limit state and to evaluate the live load models proposed by the regulations studied. The bridge studied spans 27.4 meters, and four T section prestressed concrete girders support it. To obtain the reliability index